Analysis of Community Satisfaction Level with Administration Services at Salampe Village Office - Sirajuddin Saleh; Muh. Nur Akmal; Muh. Nasrullah (Journal of Public Policy and Local Government (JPPLG), 2024)
Service is an activity carried out by someone in an institution or group to help or facilitate the community in achieving certain goals. And administration is a process of cooperation between two or more people to achieve targets by utilizing certain facilities and infrastructure in an efficient and useful manner. This research is qualitative descriptive research that aims to determine the Level of Community Satisfaction with Administration Services at the Salampe Village Office. Data collection techniques use observation, interview, and documentation methods. Data analysis techniques in this study use data condensation techniques, data presentation, conclusion, and verification. The results showed that the level of Community Satisfaction with Administration Services at the Salampe Village Office, seen as a whole, was already in the satisfactory category. This can be seen from the fulfillment of eight indicators, namely simplicity is considered good, clarity and certainty have shown good, security is good enough, openness has been carried out well, efficient has been carried out well, economics has been implemented well, equitable justice has been implemented well. But in terms of punctuality, it is still less or not optimal. This research can be used as a reference in decision making in terms of improving customer service for community satisfaction at the village level because previous research focused on the district level.